Community strategies for diversification in Ethiopia - Cortés Ferrández, P (Refugee Studies Centre, University of Oxford, 2020)
The 2015–17 drought in the Horn of Africa displaced more than 300,000 pastoralists in the eastern part of the Somali region of Ethiopia. Many who lost their livestock have instead engaged in grassroots action to improve livelihoods recovery and to build resilience.